Negative Work Psychology Perspective and Work Environment on Performance - Hasanah, Uun (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
In work, there will always be two sides, positive and negative. It depends on how we respond. However, we realize that we have limitations in controlling external factors, such as the work environment and organizational demands. The high expectations of the organization, often make the workload excessive, and in the accumulation of time, physical abilities decrease, causing the birth of work stress. Likewise with the work environment, warm relationships with coworkers or conflicts, can cause ups and downs in performance. Departing from this phenomenon, this study tries to examine negative psychological factors (stress) and the work environment on performance maintenance. The method used in this study is quantitative with the research subject being Sriwijaya airline employees, totaling 109 people. Data were collected by distributing simple random questionnaires. The collected data was then analyzed by using the statistical probability regression method. The results of the study indicate that there is a possibility of a close or reciprocal relationship that is linear, between work stress and work environment and performance. The best model in maintaining performance is to minimize negative psychological factors. The lower the level of work stress, it explains a good work system and a healthy work environment. This creates a feeling of pleasure and a positive perception of the organization and its work.